(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2024)
Background: Cotrimoxazole for severe COVID-19 may have a better prognosis because of its antibacterial, immunomodulatory, and anti-inflammatory activities. We examined the efficacy of high-dose cotrimoxazole therapy in terms of duration of hospital stays and reduction in mortality in severe COVID-19 infections. Methods: From May to November 2021, we conducted a double blind randomised controlled trial with two parallel groups in the COVID units of Bangabandhu Sheikh Mujib Medical University and Anwar Khan Modern Medical College Hospital, Dhaka. One group received standard therapy in addition to an oral dose of 960 mg of cotrimoxazole twice daily for 7 days (intervention group), while the other group received standard treatment and a placebo (standard group). Pre-protocol analysis was done. Results: A total of 188 patients were enrolled, but 166 completed the study. Of them, 93 were in the intervention group and 73 were in standard group. The mean ages of the groups were similar (intervention, 56.2 and standard, 59.2 years) (P=0.10). The mortality at 28 days between groups was also similar (11.8% in the intervention group and 15.0% in the standard group) (P=0.56). The hospital stay was 13.7 days for the intervention group and 13.5 days for the standard group (P=0.86). However, the reduction in C-reactive protein was statistically significant in the intervention group, with a mean decline of 23.6 mg/L (95% confidence interval, 0.5–46.7 mg/L). Conclusion: High-dose cotrimoxazole did not benefit in shortening in-hospital stay or reducing mortality at day 28 in patients with severe COVID-19. However, the decline in the C-reactive protein level was significant, necessitating further research.